THE RECIPROCAL RELATIONSHIP BETWEEN THE INDIAN CONSTITUTION AND PUBLIC ADMINISTRATION: LEGAL FRAMEWORK, JUDICIAL OVERSIGHT, AND GOVERNANCE REFORMS (International Journal of Food and Nutritional Sciences, 2023)
The Indian Constitution serves as the supreme legal framework guiding democratic governance and public administration in India. This study examines the reciprocal relationship between constitutional provisions and administrative practices, highlighting how constitutional mandates shape governance while administrative challenges drive legal reforms. The research explores key themes, including fundamental rights, judicial oversight, federalism, decentralization, e-governance, and administrative reforms.